Effect of long term hormone replacement on plasma prolactin concentrations in women after oophorectomy. Issue 6468 (23rd February 1985) - Barlow, D H; Beastall, G H; Abdalla, H I; Elias-Jones, J; Lindsay, R; Hart, D M
Abstract : Plasma prolactin concentrations were studied in 88 oophorectomised women who had been receiving mestranol or placebo for three to 11 years. Thirty one of them were also studied under basal conditions and by tests with thyrotrophin releasing hormone. Under basal conditions the mean prolactin concentration was higher in the oestrogen treated group but under non-rested, clinic conditions the difference was lost because of a rise in prolactin value in the placebo group only. Hence the groups showed a different prolactin response to the mild stress of clinic attendance but the same proportionate responsiveness to thyrotrophin releasing hormone. The data suggest that long term hormone replacement has no significant effect on circulating prolactin concentrations under non-rested, everyday conditions and that the prolactin stimulating effects of minor stress and oestrogen may share a similar mechanism.